The Minimum Wages Directive Proposal and the External Limits of Art. 153 TFEU - Di Federico, Giacomo (Italian Labour Law e-Journal, 2020)
The contribution aims at assessing the Commission’s recent Proposal on minimum wages in light of the treaties. In particular, it focuses on the choice of the legal basis and most notably the exclusion of pay resulting from Art. 153(5) TFEU.